HIV-1 Vpr hijacks EDD-DYRK2-DDB1(DCAF1) to disrupt centrosome homeostasis - Hossain, Delowar (J Biol Chem, 2018)
Viruses exploit the host cell machinery for their own profit. To evade innate immune sensing and promote viral replication, HIV type 1 (HIV-1) subverts DNA repair regulatory proteins and induces G(2)/M arrest. The preintegration complex of HIV-1 is known to traffic along microtubules and accumulate near the microtubule-organizing center. The centrosome is the major microtubule-organizing center in most eukaryotic cells, but precisely how HIV-1 impinges on centrosome biology remains poorly understood. We report here that the HIV-1 accessory protein viral protein R (Vpr) localized to the centrosome through binding to DCAF1, forming a complex with the ubiquitin ligase EDD-DYRK2-DDB1(DCAF1) and Cep78, a resident centrosomal protein previously shown to inhibit EDD-DYRK2-DDB1(DCAF1). Vpr did not affect ubiquitination of Cep78. Rather, it enhanced ubiquitination of an EDD-DYRK2-DDB1(DCAF1) substrate, CP110, leading to its degradation, an effect that could be overcome by Cep78 expression. The down-regulation of CP110 and elongation of centrioles provoked by Vpr were independent of G(2)/M arrest. Infection of T lymphocytes with HIV-1, but not with HIV-1 lacking Vpr, promoted CP110 degradation and centriole elongation. Elongated centrioles recruited more γ-tubulin to the centrosome, resulting in increased microtubule nucleation. Our results suggest that Vpr is targeted to the centrosome where it hijacks a ubiquitin ligase, disrupting organelle homeostasis, which may contribute to HIV-1 pathogenesis.